RETRACTED: Improving the efficiency of water use in agriculture by modelling the classification of groundwater quality - Rozhkova Alyona; Kukartsev Vladislav; Kvesko Mikhail; Suprun Elena; Andreev Vitaliy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001